(3GdfUGFM GdefLjI hGdaVGFM GdeNRjI aj GdQO Ydi GdTjYI hGdNhGQL GdeYJRdI hGdeQUFIs - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s
(3ChdgG (B:s
(3bGd Gdabjg CHh eMeO fcJ Ef TGA Gddg YR hLd ai cJGHfG gPG Ydi GdQGaVI ef HOY ePGgHge haGMT CbhGdge s
(3BNQgG (B:s
(3hJdjge aQbI bGdJ (B: (3Hd gh Gddg YR hLd JYGdi Yf caQge YdhGcHjQG hHQF Gddg hGdeDefhf efge agPg CQHY aQb ced cJGH GdfUGFM hGdaVGFM s
(3GdfSNI HgG MhGTs
(3HChdgG SeGY ddcJGH HNW eTQbi SfI (B572 (3hHGdfSNI BKGQ JbWjY HBNQgG CQHY hQbGJ ai eSGFd eJaQbI HYVgG dGHf MRes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdJhMjO hGdedd hGdfMds